GROWTH AND YIELD OF Panicum maximum GRASS PLANTING WITH LEGUM Alysicarpus vaginalis WITH DIFFERENT ORGANIC FERTILIZER DOSAGE - R. F., Al Fattah; Trisnadewi, A. A. A. S; Suarna, I W. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
The purpose of this study is to determine the growth and yield of Panicum maximum grass planted with Alysicarpus vaginalis legume with different dosage of organic ferltizer (goat manure). The study was carried out at greenhouse of Sesetan Reserch Station, Faculty of Animal Husbandry Udayana Universisty using a completely randomized design (CRD) pattern. The first pattern is a mixture of grass and legume plants: 1 grass + 1 legume (C1), 1 grass + 2 legume (C2), and 1 grass + 3 legume (C3) and the second pattern is different organic fetilizer dosage: 0 ton/ha of (K0), 15 tons/ha of (K15), and 30 tons/ha of (K30). The result of the study revealed that the planting of a mixture of Panicum maximum grass and Alysicarpus vaginalis legume did not significant effect on growth and yield variables of grass except on the total dry weight of forage. The application of 30 tons/ha organic feltilizer gave better results on the growth and yield variables, but plant height of 15 tons/ha dosage was higher compared with other plants.It could be concluded that planting with 1 grass + 2 legumes tended higher growth and yield Panicum maximum and the application of goat manure with 30 tons/ha could increase growth and yield of Panicum maximum grass. Keywords : mixed planting, Panicum maximum, Alysicarpus vaginalis, organic fertilizer